Phagocytosis assay on the breadcrumb sponge Halichondria panicea using microalgae, bacteria and latex beads - Angela Maria Marulanda-Gomez; Kristina Bayer; Lucía Pita; Ute Hentschel (PANGAEA, 2023)
Individuals of the breadcrumb sponge Halichondria panicea were collected from the field to perform phagocytic experiments. Collection site: coast of Schilksee (54.424278 N, 10.175794 E; Kiel, Germany) on August 7th 2022 at 8 am. Sponges were collected by carefully detaching them from crevices at 1-3 m depth by snorkeling. Name of the laboratory: H. panicea individuals were transported to the KIMMOCC climate chamber facilities at GEOMAR Helmholtz Centre for Ocean Research Kiel (Germany), where they were kept for two weeks under controlled temperature (room: 10°C; water: 17°C), and with water supplied from the Kiel Fjord. Culture conditions during the experiment: The phagocytic experiments started on Aug 15th 2022, and were performed in the aforementioned facilities of GEOMAR. All the experiments lasted for one week. The experiments consisted on incubating whole sponge individuals in natural seawater for 30 min with green microalgae (Nannochloropsis sp.; live culture purchased from BlueBio Tech (Germany)), live TAMRA-stained bacteria (isolate PP-XX7 ; 16S rRNA gene sequence similarity of 98.6 % with Vibrio sp. NBRC 101805 and 97.0% to Vibrio variabilis R-40492T),) or 1 μm fluorescent latex beads (Fluoresbrite YG microsphere, Cat. 17154-10, Polyscience). Water samples were taken at time intervals through the incubation period to estimate particle uptake (i.e., filtration) by the sponge using flow cytometry. Fluorescence-activated cell sorting (FACS) of sponge cells extracted from H. panciea tissue from the individuals used during the phagocytic experiment was used to quantify phagocytic activity (i.e., the population of sponge cells with internalized particles).